High frequencies of alpha common cold coronavirus/SARS-CoV-2 cross-reactive functional CD4+ and CD8+ memory T cells are associated with protection from symptomatic and fatal SARS-CoV-2 infections in unvaccinated COVID-19 patients - Coulon, Pierre-Gregoire; Prakash, Swayam; Dhanushkodi, Nisha R.; Srivastava, Ruchi; Zayou, Latifa; Tifrea, Delia F.; Edwards, Robert A.; Figueroa, Cesar J.; Schubl, Sebastian D.; Hsieh, Lanny; Nesburn, Anthony B.; Kuppermann, Baruch D.; et al. (Frontiers in Immunology, 2024)
Background: Cross-reactive SARS-CoV-2-specific memory CD4+ and CD8+ T cells are present in up to 50% of unexposed, pre-pandemic, healthy individuals (UPPHI). However, the characteristics of cross-reactive memory CD4+ and CD8+ T cells associated with subsequent protection of asymptomatic COVID-19 patients (i.e., unvaccinated individuals who never develop any COVID-19 symptoms despite being infected with SARS-CoV-2) remains to be fully elucidated. Methods: This study compares the antigen specificity, frequency, phenotype, and function of cross-reactive memory CD4+ and CD8+ T cells between Common Cold Coronaviruses (CCCs) and SARS-CoV-2. T-cell responses against genome-wide conserved epitopes were studied early in the disease course in a cohort of 147 unvaccinated COVID-19 patients who were divided into six groups based on the severity of their symptoms. Results: Compared to severely ill COVID-19 patients and patients with fatal COVID-19 outcomes, the asymptomatic COVID-19 patients displayed significantly: (i) higher rates of co-infection with the 229E alpha species of CCCs (α-CCC-229E); (ii) higher frequencies of cross-reactive functional CD134+CD137+CD4+ and CD134+CD137+CD8+ T cells that cross-recognized conserved epitopes from α-CCCs and SARS-CoV-2 structural, non-structural and accessory proteins; and (iii) Lower frequencies of CCCs/SARS-CoV-2 cross-reactive exhausted PD-1+TIM3+TIGIT+CTLA4+CD4+ and PD-1+TIM3+TIGIT+CTLA4+CD8+ T cells, detected both ex vivo and in vitro. Conclusions: These findings: (i) support a crucial role of functional, poly-antigenic α-CCCs/SARS-CoV-2 cross-reactive memory CD4+ and CD8+ T cells, induced following previous CCCs seasonal exposures, in protection against subsequent severe COVID-19 disease; and (ii) provide critical insights into developing broadly protective, multi-antigen, CD4+, and CD8+ T-cell-based, universal pan-Coronavirus vaccines capable of conferring cross-species protection.